ANALISIS PENENTUAN METODE TERBAIK TERHADAP SISTEM PENGENDALIAN PERSEDIAAN BAHAN BAKU PADA PT. X - Wijiantoro, Bakti; Suhartini (Journal of Research and Technology, 2025)
This research discusses the problem of raw material inventory control at PT. X, a company engaged in providing high-quality label printing solutions. Monthly demand fluctuations cause irregularities in raw material ordering, leading to risks of stockouts or overstock situations that impact cost efficiency and production continuity. To address this issue, the study implements three inventory control methods: Economic Order Quantity (EOQ), Periodic Order Quantity (POQ), and Min-Max. The effectiveness of each method is compared using the Simple Additive Weighting (SAW) method with criteria including optimal quantity, ordering frequency, and total inventory cost. The results show that the POQ method is optimal for controlling inventory of vinyl, art paper, and castcoat raw materials, while EOQ is more suitable for lamination materials. The appropriate use of inventory methods has proven to reduce inventory costs and minimize the risks of stock shortages or overstock at PT. X.